The Roles of Magnetic Resonance-Guided Focused Ultrasound in Pain Relief in Patients With Bone Metastases: A Systemic Review and Meta-Analysis - Han, Xiaying; Huang, Runzhi; Meng, Tong; Yin, Huabin; Song, Dianwen (Frontiers in Oncology, 2021)
Objective: Cancer pain, the most common skeleton-related event of bone metastases, significantly disturbs patients’ life. MRI-guided focused ultrasound (MRgFUS) is a therapeutic option to relieve pain, however, its efficacy and safety have not been fully explored. Therefore, we aim to conduct a meta-analysis on studies reporting MRgFUS for patients with bone metastases. Methods: Randomized controlled trials (RCT) and non-randomized controlled trials MRgFUS treatment for patients with bone metastases were collected using PubMed, MEDLINE In-Process (US National Library of Medicine), National Institutes of Health (US National Library of Medicine), Embase (Elsevier), Web of Science, CINAHL, and the Cochrane Library between August 2007 and September 2019. Data on quantitative pain assessment before/after MRgFUS, response rate and complication were extracted and analyzed. Results: Fifteen eligible studies with 362 patients were selected in this meta-analysis. The average pain score were 6.74 (95% CI: 6.30-7.18) at baseline, 4.15 (95% CI: 3.31-4.99) at 0-1 week, 3.09 (95% CI: 2.46-3.72) at 1-5 weeks, and 2.28 (95% CI: 1.37-3.19) at 5-14 weeks. Compared with baseline, the pain improvement at 0-1 week was 2.54 (95% CI: 1.92-3.16, p < 0.01), at 1-5 weeks was 3.56 (95% CI: 3.11-4.02, p < 0.01), and at 5-14 weeks was 4.22 (95% CI: 3.68-4.76, p < 0.01). Change from baseline in OMEDD at 2 weeks after treatment was -15.11 (95% CI: -34.73, 4.50), at 1 month after treatment was -10.87 (95% CI: -26.32, 4.58), and at 3 months after treatment was -5.53 (95% CI: -20.44, 9.38). The overall CR rate was 0.36 (95 % CI: 0.24-0.48), PR rate was 0.47 (95 % CI: 0.36-0.58), and NR rate was 0.23 (95 % CI: 0.13-0.34). Among 14 studies including 352 patients, 93(26.4%) patients with minor complications and 5(1.42%) patients with major complications were recorded. Conclusion: This meta-analysis identifies MRgFUS as a reliable therapeutic option to relieve cancer pain for patients with metastatic bone tumors with controllable related complications.